Pengaruh GDP, GOV, IPR, Dan TPF Terhadap Financial Inclusion Pada Perusahaan Perbankan Yang Terdaftar Di BEI Tahun 2012 – 2021 - Yeni Ariesa; Clearish Julivia; Eugene Chandra; Steven Edward Dicaprio Sitepu; Mochammad Fahlevi (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research seeks to examine the impact of GDP, GOV, IPR, and TPF on financial inclusion. The study's data were derived from the yearly published financial reports of the banking companies that are listed on the Indonesia Stock Exchange for the years 2012 through 2021. For the period of 2012–2012, a sample size of 38 banking firms listed on the Indonesia Stock Exchange (IDX) was used as the sampling method 2021. A statistical test using the panel data regression method and hypothesis testing using the F test and T test, which were earlier conducted with the classical assumption test first, are the analysis techniques used. The study's findings demonstrate that, for the years 2012 to 2021, the simultaneous effects of GDP, GOV, IPR, and TPF on Financial Inclusion in Banking Companies on the IDX are important. The GDP metric does not significantly affect stock prices, in part. The GDP variable has no significant impact on Financial Inclusion. Financial Inclusion is greatly impacted by the GOV variable. Financial Inclusion is significantly impacted by the IPR component. Financial Inclusion is not significantly impacted by the TPF variable. The research found that the coefficient of determination (R2) was 0.965392, which indicates that 96% of the Financial Inclusion variable can be explained by the independent variables, namely GDP, GOV, IPR, and TPF, and the remaining 4% can be explained by variables other than the equation. Keywords: Financial Inclusion, GDP, GOV, IPR, TPF